Assessing the Impact of RED II and EUDR on Indonesia’s Palm Oil Export Market Share and Market Concentration in the European Union - Rosyita, Dita; Maharani, Intan Mega; Astaman, Putra; Hikmah, Aulia; Rachmadhan, Aditya Arief (Tarjih : Agribusiness Development Journal, 2025)
The Renewable Energy Directive II (RED II) and the European Union Deforestation Regulation (EUDR) are the European Union’s primary policy instruments for achieving energy transition targets, sustainability standards, and emission-reductions. These regulations restrict the use of palm oil as a feedstock for biodiesel and tighten traceability requirements for deforestation-free products, thereby potentially affecting Indonesia’s export performance. This study aims to analyze changes in share and market concentration of Indonesia’s palm oil exports (HS 151100) in four major EU destination countries, the Netherlands, Italy, Spain, and Germany, following the implementation of RED II and the early phase of EUDR implementation. This research employed time series data from 2011 to 2024, divided into two periods: seven years before the policy implementation and seven years representing the early phase of RED II (2019-2024). However, the data remain limited for comprehensively assessing the impact of the EUDR, as they only cover the 2023-2024 period. The methods used include the Market Share Index (MSI), the Herfindahl-Hirschman Index (HHI), and a two-mean difference test using a paired sample t-test. The results show a significant decline in Indonesia’s market share in three main countries, Netherlands, Italy, and Spain following the implementation of the policies, while Germany remains relatively stable. The HHI value decreased from 0.016 to 0.06, indicating a shift in market structure from a moderately concentrated market to a more differentiated oligopoly market. This change indicates that Indonesia has undertaken market diversification in response to increasing non-tariff barriers and policy risks imposed by the European Union.